Arsitektur Jaringan Komputer Berbasis Framework Togaf-Adm Menggunakan Proses NDLC - Ahmad Fariz; Syamsul El Yumin; Masbah RT Siregar; Taswanda Taryo (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2019)
One factor for the achievement of the objectives of the concept of learning in the management of modern education is to utilize information technology that is supported by a reliable computer network architecture. In this research, the method of designing a computer network architecture is based on the 4 stages of the TOGAF-ADM Framework, namely vision architecture, business architecture, information systems architecture (data architecture and application architecture) and technology architecture. Then the system implementation uses the Network Development Life Cycle (NDLC) process which consists of analysis, design, simulation prototyping, implementation, monitoring, management and ending with an evaluation of computer network development. From the trial results, it is obtained that by using load balance technology and microtic device support, sending and receiving data packets is now faster and more stable because the communication lines have been segmented and the data collision in the network is resolved. The new network implementation successfully stabilized upload and download data speeds, overcoming limited connections and 0% packet loss.